Factores asociados a la falta de adherencia al consumo de multimicronutrientes “Chispitas”, en niños de 06 a 36 meses de edad, del puesto de salud I-2 Masusa, año 2018. - Chávez Nolorbe, Marden (2018)
Objetive: Determine the factors associated to the lack of adherence to the consumption of multimicronutrients "Chispitas", in children from 06 to 36 months of age, from the Health Post I-2 Masusa, year 2018. Material and Method: An observational, cross-sectional analytical study was conducted, which included all children, between 06 to 36 months of age from the jurisdiction of the I-2 Masusa Health Post who consume the multimicronutrients, making a total of 336; with a representative sample of 180 children, selected with the simple probabilistic method. In order to collect the information, the mothers of the children who consume the multimicronutrients were surveyed, after accepting the informed consent. Then, the possible associations between the independent and dependent variables were determined, using the Chi2 test with statistical significance (p <0.05). Results: The following was found; according to the age group, the majority of mothers were between 20 and 24 years old, with 30.6% (55/180), 12.2% (22/180), were teenage mothers. 58.9% (106) of the mothers reached secondary education and only 2.2% (4) reached higher education. 81.7% (147) are housewives. 76.1% (137), maintain the coexistence with their partners. In addition, it was observed that 46.1% of mothers come from rural areas. Regarding Sociodemographic factors: age could not be shown to have a statistically significant relationship with lack of adherence (Chi2 = 3.30, p = 0.056). But yes, the place of origin, in which rural is associated statistically significant to the lack of adherence to MMN consumption (Chi2 = 7.60, p = 0.004). Regarding attitudinal factors: We found that confidence in MMNs, forgetfulness and perception of benefit were statistically associated with the lack of adherence in MMN consumption (Chi2 = 37.91, p = 0.0001); (Chi2 = 47.06, p = 0.0001); (Chi2 = 57.89, p = 0.00001), respectively. Regarding the characteristics of the multimicronutrients: It was found that the form of presentation of the MMN, appearance, taste and adverse effects if they are statistically significant associated to the lack of adherence in the MMN consumption (Chi2 = 25.25; p = 0.0001); (Chi2 = 31.51; p = 0.0001); (Chi2 = 73.91, p = 0.00001); (Chi2 = 81.32; p = 0.000001), respectively. Regarding health care: It was found that the perception of satisfaction with the care received, waiting time and the home visit are statistically significant associated with the lack of adherence in MMN consumption (Chi2 = 5.73; p = 0.016); (Chi2 = 20.83, p = 0.0001); (Chi2 = 4.81, p = 0.02), respectively. Moreover, it was not found that the distance to the health establishment is associated with the lack of adherence in the MMN consumption (Chi2 = 1.82, p = 0.11). respectivamente. Más, no se encontró que la distancia al establecimiento de salud esté asociado a la falta de adherencia en el consumo de los MMN (Chi2= 1.82; p= 0.11). El nivel de adherencia en el consumo de los MMN fue de 54.4 % es decir, el 45.6 % de las madres no cumplen con administrar los MMN a sus niños. Conclusiones: El nivel de adherencia hacia los multimicronutrientes en el Puesto de Salud Masusa I- 2, del distrito de Punchana, provincia de Maynas, departamento de Loreto fue de 54.4%. Los factores actitudinales y las características de los MMN están más asociados a la falta de adherencia en el consumo de los MMN en el Puesto de Salud Masusa I- 2 seguidos de los factores sociodemográficos y características de la atención de salud.